Healthcare Access Disparities in Coastal Regions: A Review - Rima Anggraini Asbar; Syamsiah T (Journal of Health Science and Pharmacy, 2025)
Background: Coastal communities in Indonesia experience significant challenges in accessing healthcare services, mainly due to inadequate infrastructure, the unequal distribution of healthcare personnel, and the economic limitations of local populations. These issues result in health disparities between coastal and non-coastal regions.Objectives: This study aims to identify and analyze the key factors affecting access to healthcare services in coastal areas to provide a comprehensive understanding of the barriers faced by these communities.Methods: A systematic review was conducted using a qualitative descriptive approach. Data were collected from 20 academic journal articles published between 2016 and 2024. The inclusion criteria focused on studies that specifically examined healthcare access issues in coastal regions.Results: The findings reveal that healthcare access in coastal areas is hindered by multiple factors. These include geographical constraints such as long distances and limited transportation infrastructure; economic challenges, including low income levels and high healthcare costs; shortages of medical personnel; public perceptions and attitudes toward healthcare; and government policies that have not been fully optimized to address the specific needs of coastal communities. Each of these factors contributes differently but collectively impacts the extent to which coastal populations can access and utilize available health services.Conclusion: Improving healthcare access in coastal areas requires a comprehensive and multi-sectoral approach. Strategies should include infrastructure development, increasing the number of healthcare personnel, providing transportation subsidies, and implementing more intensive health education programs tailored to the needs of coastal populations. Keywords: Public Opinion, Government, Health Services,Health Care Costs, Indonesia